2001
DOI: 10.1177/10454411010120040201
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Acid Adaptation in Oral Streptococci

Abstract: A growing body of information has provided insights into the mechanisms by which the oral streptococci maintain their niches in the human mouth. In at least one case, Streptococcus mutans, the organism apparently uses a panel of proteins to survive in acidic conditions while it promotes the formation of dental caries. Oral streptococci, which are not as inherently resistant to acidification, use protective schemes to ameliorate acidic plaque pH values. Existing information clearly shows that while the streptoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
111
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(118 citation statements)
references
References 142 publications
6
111
0
1
Order By: Relevance
“…During intake of sweetened foodstuff, for example, carbohydrate concentrations in the oral cavity can rapidly increase from around 10 mm to well over 10 mM (Lemos et al, 2005;Lemos & Burne, 2008). Concurrent with the influx of dietary carbohydrates is a dramatic decrease in pH to values of 4 or lower in dental biofilms (Quivey et al, 2001). This socalled 'feast-and-famine' lifestyle provides some organisms, such as Streptococcus mutans, with a significant advantage in competition with other species in dental biofilms, resulting in an emergence of numerically significant members in dental plaque that may cause caries (Marsh, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…During intake of sweetened foodstuff, for example, carbohydrate concentrations in the oral cavity can rapidly increase from around 10 mm to well over 10 mM (Lemos et al, 2005;Lemos & Burne, 2008). Concurrent with the influx of dietary carbohydrates is a dramatic decrease in pH to values of 4 or lower in dental biofilms (Quivey et al, 2001). This socalled 'feast-and-famine' lifestyle provides some organisms, such as Streptococcus mutans, with a significant advantage in competition with other species in dental biofilms, resulting in an emergence of numerically significant members in dental plaque that may cause caries (Marsh, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…This socalled 'feast-and-famine' lifestyle provides some organisms, such as Streptococcus mutans, with a significant advantage in competition with other species in dental biofilms, resulting in an emergence of numerically significant members in dental plaque that may cause caries (Marsh, 1994). These environmental variations are known to have profound impacts on bacterial gene expression and have been unequivocally shown to be the factors that influence the microbial composition and biological activities of dental plaque biofilms (Lemos et al, 2005;Marsh, 1994;Quivey et al, 2001). To persist in dental biofilms, oral bacteria must be able to sense, respond and adapt to such rapid and unexpected environmental changes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While a normal inhabitant of the oral cavity, S. mutans is mostly known for its importance in the aetiology of dental caries and occasional association with subacute infective endocarditis. Decades of research have conclusively demonstrated that S. mutans is a major cariogenic organism by virtue of its contribution to the formation of the dental biofilm matrix, its capacity to produce large quantities of organic acids, and its ability to outcompete non-cariogenic commensal species at low pH conditions (Banas & Vickerman, 2003;Bowen & Koo, 2011;Gross et al, 2012;Lemos et al, 2005;Quivey et al, 2001).…”
mentioning
confidence: 99%